2018
DOI: 10.5194/acp-18-1573-2018
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of satellite observations of AOD over mainland China using ATSR-2, AATSR and MODIS/Terra: data set evaluation and large-scale patterns

Abstract: Abstract. The retrieval of aerosol properties from satellite observations provides their spatial distribution over a wide area in cloud-free conditions. As such, they complement ground-based measurements by providing information over sparsely instrumented areas, albeit that significant differences may exist in both the type of information obtained and the temporal information from satellite and ground-based observations. In this paper, information from different types of satellite-based instruments is used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 112 publications
9
70
0
Order By: Relevance
“…For example, Song et al (2016) showed that the spring dust storm frequency in arid and semiarid regions of China has decreased by 15.45 storms per year on average over the period of 1982 to 2007. Fan et al (2014) showed that the decrease in springtime dust storms in Inner Mongolia, northern China, from 1982 to 2008 was correlated with advanced vegetation growth, with 1 d earlier green-up data corresponding to a 3 % decrease in spring dust storms. analyzed the frequency of sand and dust storms observed from ground stations in East Asia during 2007-2016 and found a decreasing trend that is associated with an increase in vegetation coverage and the weakening of the polar vortex.…”
Section: Interannual Variability In Smoke-or Dust-dominated Outflowsmentioning
confidence: 99%
“…For example, Song et al (2016) showed that the spring dust storm frequency in arid and semiarid regions of China has decreased by 15.45 storms per year on average over the period of 1982 to 2007. Fan et al (2014) showed that the decrease in springtime dust storms in Inner Mongolia, northern China, from 1982 to 2008 was correlated with advanced vegetation growth, with 1 d earlier green-up data corresponding to a 3 % decrease in spring dust storms. analyzed the frequency of sand and dust storms observed from ground stations in East Asia during 2007-2016 and found a decreasing trend that is associated with an increase in vegetation coverage and the weakening of the polar vortex.…”
Section: Interannual Variability In Smoke-or Dust-dominated Outflowsmentioning
confidence: 99%
“…The decreasing trend of carbonaceous aerosols (e.g., organic carbon, elemental carbon) after 2008 and dust aerosol after 2010 may also contribute to the decline of AOD [40,41]. In addition, AOD variation may be influenced by thin cloud contamination in the satellite retrievals of AOD, meteorological factors, climate change and economic recession [42,43]. The greatest increase of AOD occurs in NP, accompanied with a largest decrease in PAR dir and PAR total and a second largest increase in PAR dif from 2001 to 2008.…”
Section: Typical Regionsmentioning
confidence: 99%
“…There is general agreement on large scales, but regionally, differences can still be significant (Li et al, ; Prasad & Singh, ; Boiyo et al, ; Kahn et al, ; Tao et al, ; Li et al, ; Wang et al, ; Wei et al, ; Wei, Peng, et al, ). Discrepancies are also observed among different satellite data sets (Banks et al, ; Bibi et al, ; de Leeuw et al, ; de Leeuw et al, ). Moreover, even for the monthly mean product in which random errors have been largely averaged out, there are still disagreements.…”
Section: Introductionmentioning
confidence: 99%